(untitled) (European Journal of Health Research, 2024)
Introduction: Non-adherence to diet and fluid intake of the patient on hemodialysis can lead to the accumulation of toxic metabolites in the blood, resulting in increased morbidity and premature death. Objective: to determine biochemical parameters and diet adherence in patients with type 2 diabetes on hemodialysis attending the dialysis unit of the General Hospital IESS Riobamba. Methods: A quantitative correlational, prospective, quasi-experimental, longitudinal design study was carried out in 87 subjects with diabetic nephropathy of both sexes between 40 and 70 years of age, who were receiving dialysis treatment. Biochemical measurements were taken (hematological, metabolic and lipid profile, albumin and electrolytes) and the questionnaire of non-adherence to diet and fluids for hemodialysis (DDFQ) was applied. Results: Significant differences were found (p<0.05) in the male gender in the following parameters: hemoglobin, creatinine and albumin. While in women significant differences were found in uric acid concentration. In both sexes significant differences were observed in phosphorus and potassium concentrations (p<0.05). About 80% of the patients manifested a degree of deviation from 1 to 3 (between no deviation and moderate deviation) to diet and fluid restrictions. Conclusion: most of the patients showed a good adherence to diet and liquid restrictions, which was related to the main biochemical parameters studied